P82 Is the presence of bacterial infection in nasal brushings associated with challenges in PCD diagnostics?. (11th November 2022) - Sepahzad, A; Burgoyne, T; Carr, S; Davies, JC; Daudvohra, F; Dixon, M; Hogg, C; Rai, R; Shoemark, A
Abstract : Introduction & Objectives: Primary ciliary dyskinesia (PCD) is a rare inherited disorder caused by an abnormality of ciliary function. Early diagnosis of PCD is crucial to delay lung damage and preserve lung function. There is no gold standard diagnostic test, instead diagnosis requires taking nasal brush biopsies for high-speed video microscopy assessment of cilia motility, transmission electron microscopy of cilia ultrastructure, immunofluorescence to look at localisation of ciliary proteins and genetics to identify pathogenic mutations. Secondary ciliary dysfunction, which can be caused by infection and inflammation, can make this process more challenging. Studies have suggested repeat brushings are needed in up to 25% of patients and some cases will require up to 4 brushings. 1 Our aim to was to investigate the relationship between bacterial growth on nasal brushings and ability to secure a diagnosis. Methods: PCD diagnostic test results were analysed retrospectively, according to microbiology by standard culture techniques from the nasal brushing. Consecutive paediatric patients referred for PCD diagnostics included an original cohort of 526 patients referred between 2014–2017 and a validation cohort of 865 patients (2017–2021). Results: Combined, 39% of patients (46% in the original cohort, 34% in the validation cohort) had bacterial growth in the nasal brushing. We observed a numerically greater proportion of growths in patients with PCD compared to those without PCD in both cohorts, however this was not statistically significant. In the non-PCD group, there was no significant difference in mean (±SD) ciliary beat frequency according to presence (10.33 ± 2.08 Hz) or absence (10.20 ± 2.18 Hz) of bacterial growth (p=0.428). Samples which were not adequate for analysis had significantly increased proportions of bacterial growths when compared to those in which a diagnostic result was obtained ( figure 1 ). Conclusion: Contrary to much in-vitro data, there was no correlation between bacterial infection and ciliary beat frequency. We did however observe an association between the presence of bacteria and failure to reach a diagnosis. We would therefore recommend consideration of antibiotic treatment when repeat nasal brushing is needed. References: J Braun et al . European Annals of Otorhinolaryngology, Head and Neck Diseases 2017. 134 (6):377–382.